Quality analysis of effluents from biodigesters in lodges located in the Cuyabeno Wildlife Reserve - Gutiérrez Cruz, Isidro; Rivera Carrión, Edgar; Roldán Reascos, Gloria (Enfoque UTE, 2016)
In the Cuyabeno Wildlife Reserve near Laguna Grande and Cuyabeno river, several ecological hotels have been built to meet the touristic demand; therefore these eco-lodges generate wastewaters. The Ministry of Environment, responsible for biodiversity conservation, has ordered the implementation of biodigesters for the treatment of these waters. After three years of implementing the system, it is proposed to check the quality of these waters, through the analysis of physical-chemical parameters: temperature, conductivity, pH, sulfates, nitrates and nitrites, detergents, COD, BOD5, oils and fats; and microbiological such as faecal coliforms. These results were compared with the current environmental legislation: TULSMA "Limits discharged to a body of fresh water." Sampling was subject to the provisions of standard Regulation INEN 2 169: 2013 and sampled at the time of high and low rainfall. The results determined that biodigesters only meet the standard regulations in three parameters: nitrates and nitrites; sulfates and temperature; and violate the following regulations: BOD5, COD and pH; while in the remaining four parameters, there is a variation among the results. In conclusion all digesters violate the regulations, at least on one of the parameters.